AN IMPACT EVALUATION OF THE “POLICE GOES TO SCHOOL” PROGRAM IN NORTH SUMATRA: ADOLESCENTS’ ATTITUDES, KNOWLEDGE, AND TRAFFIC BEHAVIORS - Irmawati Irmawati; Omar Khalifa Burhan; Nurmasari Nurmasari; Rozi Nasution; Esther Pasaribu (Journal of Indonesia Road Safety, 2020)
The present paper evaluates the implementation of the Police Goes to School program in North Sumatra and suggest how public officials (e.g., government and police) could use religiosity and traffic rules exposure to promote safe road behaviors among Indonesian adolescents. The results suggest three main findings. First, the results showed the effectiveness of the Police Goes to School program. Students from the actively implemented schools possessed more positive attitudes toward traffic rules, more knowledge of traffic rules, and engaged in safer traffic behaviors than students from the passively implemented schools. Second, structured interviews revealed that although the police officers and teachers involved in the program expressed their satisfaction concerning the implementation of the program, they also provided suggestions to improve the program. Third, the results also suggest the potential benefit of integrating the socialization of traffic rules into the Indonesian religious education curriculum to promote safe traffic behaviors among adolescents in Indonesia.